Possibility to extend the shelf life of NFC tomato juice using cold atmospheric pressure plasma - Starek, Agnieszka (Sci Rep, 2020)
Cold Atmospheric pressure Plasma (CAP) is a non-thermal method used in food processing. CAP generated with the use of nitrogen in a Glide-arc device for 300 to 600 s exhibited high potential for microbial decontamination and did not induce substantial changes in the physicochemical properties of NFC tomato juice. Samples exposed to cold atmospheric plasma had mostly an intact structure, as revealed by digital microscopy. The investigations indicate that CAP can be applied for biological and chemical waste-free decontamination of food and extension of its shelf life.